Addressing practices in multilingual student-teacher interaction in Pakistani English - Soomro, Muhammad Arif; Larina, Tatiana V. (Penerbit Universiti Kebangsaan Malaysia, 2024)
Address forms in varieties of pluricentric languages can be influenced by local values and cultural specificities, which reveal the bilingual and bicultural identity of the speakers. The paper explores the Pakistani variety of English and focuses on addressing practices in university student-teacher interaction in top-down and bottom-up contexts. The study aims to identify the categories of address forms used by students and teachers in Pakistani English and to find out lingua-cultural, axiological, and socio-pragmatic factors that impact their choices and preferences. The data were collected through a questionnaire and open-ended written interviews with the participation of 252 students and 130 teachers and supplemented by 13 hours of audio-recorded classroom observation. The data were subjected to linguacultural, sociolinguistic, pragmatic and discourse analysis drawing on pragmatics, the theory of forms of address, the theory of politeness, the World Englishes Paradigm and cultural studies. The findings revealed that both teachers and students use a mixture of different categories of English and native address forms, and their combination resulted in hybrid forms to express their values and attitudes. The findings provide new data on the impact of sociocultural and axiological factors on address forms and may have implications for the World English paradigm, cross-cultural pragmatics, cultural linguistics and second language (S.L.) teaching.